SOSIALISASI, KONSULTASI DAN PELAYANAN FISIOTERAPI PADA LANSIA DENGAN HIPERTENSI DI DESA KLAMPOK SINGOSARI - Nur Fatihatul Faedah,; Nungki Marlian Yuliadarwati,; Ratna Vidya Amelia, (JURNAL PENGABDIAN MANDIRI, 2024)
Hypertension is a type of non-communicable disease that is chronic, lasts throughout life and is a silent killer, with a very high prevalence rate in the elderly. The problem encountered in the situation analysis in Klampok Village was that the elderly on average had hypertension. For this reason, it is necessary to socialize physiotherapy in recognizing and preventing the progression of hypertension and providing physiotherapy services for elderly people who have health problems in accordance with the realm of physiotherapy. The method used is socialization using leaflets, consultations and physiotherapy services. The results of the activity were carried out on Tuesday 24 October 2023 at the house of the Posyandu Arjuna Cadre, Klampok Village, starting from 09.00-13.00 WIB. The number of participants, namely elderly people with hypertension, was 24 participants. The conclusion was that the socialization activities, consultations and physiotherapy services went well and smoothly according to plans and objectives, the participants who attended understood and were enthusiastic when the presenters explained the material